Momen Objektivasi Etnis Simalungun Berdasarkan Organisasi Sosial - Hadiani Fitri (Keguruan, 2022)
A social movement also provides guidance on how members should think. Such norms are something resembling a "party line"- the definition of "correct" position for members to look at a specific issue. There is subtle pressure on the individual to support this position even in the absence of personal knowledge of the argument to argue. Not every member can be expected to learn and think through the justified philosophy of the movement and its values. Ideology provides it with "ready-made", which seems to have the power to organize opinions (arguments) This research uses a qualitative approach, with a research design that develops and is open adapted to field conditions. Adjustment to field conditions is used with respect to the relevance of the problem under study, the use of theories and concepts and method used, the objectivity of the research results is based not on the proof of generalization.  The process of objectivization carried out simultaneously through externalization and internalization which in the process of its socialization gives rise to changes that are not uncommon as a matter of concern, such as nervousness or relative deprivation. The moment of simalungun ethnic objectivization is based on social organizations that carry ethnic names, such as Partuha Maujana Simalungun (PMS), Simalungun Protestant Christian Church (GKPS), Simalungun Islamic Family Association (IKEIS), Simalungun Student and Student Association (HIMAPSI).